Scientific Research in Elementary Mathematics Classes Using Methods - M.A. Gafurova; Z.I. Muhammadiyeva (Zien Journals, 2023)
This article describes ways to increase students' creativity and develop critical thinking skills by using scientific research methods in elementary mathematics classes.
Keywords: Analysis; synthesis; method; problem